Perlindungan Lingkungan Laut Pesisir Bengkulu Dalam Perspektif Hukum - Ahmara Nisa; Assyifa Nadaul Mufidah; Muhammad Kurnia Zaetama (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study analyzes the protection of the coastal marine environment of Bengkulu from an Indonesian legal perspective, focusing on the challenges of ecosystem degradation caused by human activities such as overfishing, industrial pollution, and coastal erosion. A normative-juridical approach is used to examine the national legal framework, including Law Number 32 of 2009 concerning Environmental Protection and Management, Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands, and Bengkulu regional regulations such as Regional Regulation Number 6 of 2011 concerning Zoning Plans for Coastal Areas and Small Islands. The study also found that legal implementation remains weak due to a lack of inter-agency coordination, weak law enforcement, and minimal participation of indigenous communities in sustainable management. A modern environmental law perspective emphasizes a restorative justice approach and integrated coastal zone management (ICZM) to harmonize economic development and conservation. Recommendations include strengthening ecological criminal sanctions, empowering coastal communities through environmental law education, and integrating Bengkulu customary law into zoning policies. Thus, protecting Bengkulu's coastal marine areas requires holistic legal reform to achieve sustainable environmental justice.